Perforated Meckel's Diverticulum in an Adult - Camelo, Rita (2018)
Meckel's diverticulum is the commonest congenital anomaly of the gastrointestinal tract. Its complications have an extensive variety of clinical and imaging manifestations, extending from benign and indolent findings to acute life-threatening conditions. Complicated Meckel's diverticulum often constitutes a challenging diagnosis for both the clinician and the radiologist. Therefore, imaging techniques play an important role in this condition in evaluating its complications, determining decision making. We describe a case of a 49-year-old man suffering from right abdominal pain with fever and constipation, during the past 5 days. Laboratory data revealed C-reactive protein of 306 mg/L and leukocytosis. Contrast-enhanced CT features were highly suggestive of perforated Meckel's diverticulum. The purpose of this article is to emphasize that besides its rarity, Meckel's diverticulum complications can occur in adult patients.